Financial liberalization and house prices: Evidence from China - Shi, Yining (Journal of Banking & Finance, 2022)
I investigate whether financial liberalization can affect house prices. I exploit the 2008 US financial crisis as an exogenous shock that negatively affected foreign banks’ operations in China. Using cross-sectional variation in foreign banks’ establishment and asset value, I document that cities with a higher level of financial openness have more volatile house price movements. I also show that the drops in house price growth rates in 2008 were larger for cities with higher withdrawal or exit rates of overseas banks. I exclude alternative explanations for the negative treatment effect, such as shocks to international trade and local economic conditions in 2008. The evidence suggests a credit supply channel. Further analyses show that the negative effect of financial liberalization on the house price growth rate is more pronounced for more geographically constrained cities.